Análisis del lenguaje periodistico del cronista Jose Delgado - Espín Pelagallo, Mariana del Carmen (2019)
Journalism is a profession that seeks to inform in the best possible way on various communication platforms; whether traditional or digital. The new technologies produce social and media changes, due to this, the media must be in constant reinvention to keep the reader or viewer attentive to the information that is broadcast. There is a high level of competence when creating new forms of communication, however, when this new objective is reached, the information in its essence is being set aside and the most irrelevant but curious side of the news or event is appealed. Giving as a result the exposure of depleted or exaggerated information, with the sole purpose of attracting attention in an uncompressed way. The present research work is a qualitative nature, through the interview technique it was concluded that the journalistic style proposed by José Delgado, is based on the basic journalistic language and a journalistic style designed to fit in a certain social sector. Coincidentally, this sector is a faithful follower of this type of journalism, because it allows us to observe social problems that are everyday and easy to understand